Oncolytic peptide LTX-315 induces anti-pancreatic cancer immunity by targeting the ATP11B-PD-L1 axis. Issue 3 (14th March 2022) - Tang, Tianyu; Huang, Xing; Zhang, Gang; Lu, Minghao; Hong, Zhengtao; Wang, Meng; Huang, Junming; Zhi, Xiao; Liang, Tingbo
Abstract : Background: LTX-315 is an oncolytic peptide deriving from bovine lactoferrin, with the ability to induce cancer immunogenic cell death. However, the mechanism used by LTX-315 to trigger the antitumor immune response is still poorly understood. The expression of programmed cell death ligand 1 (PD-L1) largely determines the efficacy and effectiveness of cancer immunotherapies targeting this specific immune checkpoint. This study aimed to demonstrate the potential effect and mechanism of LTX-315 in PD-L1 inhibition-induced anti-pancreatic cancer immunity. Methods: Both immunodeficient and immunocompetent mouse models were used to evaluate the therapeutic efficacy of monotherapy and combination therapy. Flow cytometry and immunohistochemistry were used to assess the immune microenvironment. Multiomic analysis was used to identify the potential target and down-streaming signaling pathway. Both in-house tissue microarray and open accessed The Cancer Genome Atlas data sets were used to evaluate the clinical relevance in pancreatic cancer prognosis. Results: LTX-315 treatment inhibited PD-L1 expression and enhanced lymphocyte infiltration in pancreatic tumors. ATP11B was identified as a potential target of LTX-315 and a critical regulator in maintaining PD-L1 expression in pancreatic cancer cells. As regards the mechanism, ATP11B interacted with PD-L1 in a CKLF-like MARVEL transmembrane domain containing 6 (CMTM6)-dependent manner. The depletion of ATP11B promoted CMTM6-mediated lysosomal degradation of PD-L1, thus reactivating the immune microenvironment and inducing an antitumor immune response. The significant correlation among ATP11B, CMTM6, and PD-L1 was confirmed in clinical samples of pancreatic cancer. Conclusions: LTX-315 was first identified as a peptide drug inducing PD-L1 downregulation via ATP11B. Therefore, LTX-315, or the development of ATP11B-targeting drugs, might improve the efficacy of cancer immunotherapy.